1983
DOI: 10.1073/pnas.80.18.5485
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian pancreatic preproglucagon contains three glucagon-related peptides.

Abstract: We have isolated cDNA clones encoding bovine pancreatic preproglucagon. Twenty-five putative preproglucagon clones were selected by screening 3,100 clones of a fetal bovine pancreas cDNA library with a synthetic oligodeoxynucleotide probe. The probe was a mixture of synthetic 17-base DNA oligomers constructed to correspond to the six carboxyl-terminal amino acids (residues 24-29) of mature glucagon. Restriction mapping of six of these clones suggested that they represented a single mRNA species. Primary sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(56 citation statements)
references
References 56 publications
(48 reference statements)
1
54
0
1
Order By: Relevance
“…Glucagon is synthesized mainly in the A-cells present at the periphery of the islets of Langerhans (Baum et al, 1962) and is also detected in specific cells in the stomach and intestine in some species (Baetens et al, 1976), as well as in specialized neurons of the central nervous system. Isolation of cDNAs encoding glucagon (Lund et al, 1982;Lopez et al, 1983) showed that the peptide is produced from a 160-amino acid precursor, proglucagon, which also contains two additional glucagon-like sequences at its carboxyl terminus (GLP-1 and GLP-2), which were subsequently shown to display specific biological activities (Drucker, 1998).…”
Section: The Glucagon Receptormentioning
confidence: 99%
“…Glucagon is synthesized mainly in the A-cells present at the periphery of the islets of Langerhans (Baum et al, 1962) and is also detected in specific cells in the stomach and intestine in some species (Baetens et al, 1976), as well as in specialized neurons of the central nervous system. Isolation of cDNAs encoding glucagon (Lund et al, 1982;Lopez et al, 1983) showed that the peptide is produced from a 160-amino acid precursor, proglucagon, which also contains two additional glucagon-like sequences at its carboxyl terminus (GLP-1 and GLP-2), which were subsequently shown to display specific biological activities (Drucker, 1998).…”
Section: The Glucagon Receptormentioning
confidence: 99%
“…Glucagon-like peptide-2 has no effect on insulin secretion at any glucose concentration tested. It is concluded that glucagon-like peptide-t, in contrast to glucagon-like peptide-2, exhibits a glucose-dependent insulinotropic action on isolated rat pancreatic islets similar to that of glucagon and gastric inhibitory polypeptide.Key words: Glucagon-like peptide-t, glucagon-like peptide-2, insulin release, glucose dependency, isolated islets.Pancreatic preproglucagon m-RNA, the precursor of pancreatic glucagon, has been cloned and sequenced from different species using recombinant DNA-techniques [1][2][3][4][5]. Two other peptides have been found arranged in tandem on the same m-RNA in close proximity C-terminal to the glucagon precursor: glucagonlike peptide-I (GLP-1) and glucagon-like peptide-2 (GLP-2) comprising 36 and 34 amino acid residues, respectively.…”
mentioning
confidence: 99%
“…Pancreatic preproglucagon m-RNA, the precursor of pancreatic glucagon, has been cloned and sequenced from different species using recombinant DNA-techniques [1][2][3][4][5]. Two other peptides have been found arranged in tandem on the same m-RNA in close proximity C-terminal to the glucagon precursor: glucagonlike peptide-I (GLP-1) and glucagon-like peptide-2 (GLP-2) comprising 36 and 34 amino acid residues, respectively.…”
mentioning
confidence: 99%
“…The nucleotide sequences of cDNA derived from hamster [1] and ox [2] glucagon mRNA and the human preproglucagon gene [3] show that pre-proglucagon contains two further glucagon-like peptides (GLP-1 and -2) C-terminal to the glucagon sequence. The amino-acid sequence of GLP-1 is completely conserved between the three mammalian species studied and shows a high degree of homology with similar deduced amino-acid sequences in angler-fish pre-proglucagons [4].…”
mentioning
confidence: 99%